2021
DOI: 10.1039/d1ja00165e
|View full text |Cite
|
Sign up to set email alerts
|

Nd, Am and Cm isotopic measurements after simultaneous separation in transmutation irradiated samples

Abstract: In this work, a High-Performance Liquid Chromatography (HPLC) separation followed by Thermal Ionization Mass spectrometry (TIMS) measurements was optimized to measure Am, Cm and Nd isotope ratios in irradiated samples....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…All theoretical investigations were performed on the same sample (DIAMINO sample [4,22]). The characteristics of the sample have been summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All theoretical investigations were performed on the same sample (DIAMINO sample [4,22]). The characteristics of the sample have been summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the sample have been summarized in Table 1. The isotope ratios, abundances and uncertainties of the sample were determined in previous studies [4,22]. The U and Pu amount concentration of the sample were estimated using a L-line X-ray fluorescence analysis located in a shielded line [23].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alexandre Quemeta et al [ 150 ] demonstrated that TIMS measurements with the TE method combined with isotope dilution could yield expanded uncertainties (k = 2) at 0.1% and 0.81% for the 241 Am/ 243 Am ratio and the concentration of 241 Am. In a more recent study, they employed TIMS with total evaporation to measure Nd, Am, and Cm isotopes, and the uncertainty estimations were below 0.2% (k = 2) [ 151 ]. Multiple collector thermal ionization mass spectrometry (MC-TIMS) was evaluated for trace and ultra-trace levels of the isotope ratio analyses of actinides.…”
Section: Mass Spectrometry For 241 Am Measurementmentioning
confidence: 99%